Local Approaches to Address Global Challenges: Educating Local Innovators for Positive Social Change - Silva-Flores, Martha Leticia (Archīum Ateneo, 2023)
Aligning global concerns with local challenges is essential for achieving long-term sustainability. This entails addressing local communities’ needs and issues to develop effective and sustainable solutions. This approach not only benefits communities but also has the potential to impact the environment and society positively. Local innovators play a fundamental role in promoting sustainable development by devising creative and sustainable solutions to problems affecting their communities. However, in the case of local entrepreneurs in the Guadalajara Metropolitan Area (GMA), their ventures often have a fleeting lifespan, limiting their impact on global challenges. This research study, therefore, focuses on empowering these local innovators by providing them with the knowledge necessary to become change agents in their communities. The central question is: How can local innovators be empowered with the knowledge needed for generating positive social change? To answer this question, we explore how local entrepreneurs acquire knowledge through formal and informal training to drive social innovation projects that address local issues. The results reveal that more than 50% of entrepreneurs participate in entrepreneurship-related meetings and events to establish connections with other entrepreneurs. These spaces also become significant sources of knowledge and resources for their projects. Furthermore, it was observed that while entrepreneurial ideas are rooted in local concerns, they often have a global scope. This study addresses the importance of social-driven entrepreneurs for sustainable innovation and highlights the need to establish connections between formal and informal education. The paper is structured into six sections to provide a comprehensive overview of the research, from contextualization to findings and final implications.